(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Within the framework of the sustainable global trend of transition to the digital economy and information society, the distribution of digital innovations depends on the environment and scale (from nano to global) in which they occur. They determine the speed and qualitative nature of the changes generated in the respective markets, including the labor market. In those spheres where a significant proportion of employees perform work related to the collection, processing and analysis of information (for example, in the scientific and educational sphere, health care, management and public services, and now also in the production of transport, construction and agriculture), digitalization processes can contribute to a significant increase in labor productivity, taking into account the availability of the necessary equipment and the relevant competencies of the personnel. We emphasize that the provision of open access to state information resources will help to increase the transparency of strategic and tactical decisions and social stability.